Performance of lactate in discriminating bacterial meningitis from enteroviral meningitis - Domingues, Renan Barros (2019)
The cytological and biochemical examination of cerebrospinal fluid (CSF) has been used for the presumed diagnosis of bacterial meningitis until the final microbiological results are achieved. We assessed the ability of CSF lactate in comparison with other CSF parameters to discriminate bacterial and enteroviral community acquired meningitis. We included 1,187 CSF samples of acute community-acquired meningitis, being 662 cases of bacterial and 525 of enteroviral meningitis. Lactate concentration (mg/dL), leukocyte count/mm3 , protein (mg/dL), and glucose (mg/dL) were compared between bacterial and viral meningitis. Receiver operator characteristic (ROC) curves were used to assess diagnostic performance. CSF leukocytes, CSF protein and CSF lactate were significantly higher in bacterial meningitis cases (P<0.0001). CSF glucose was significantly lower in bacterial meningitis cases (P<0.0001). CSF lactate showed the best predictive ability with an area under the curve of 0.944 (95% CI 0.929 – 0.959). Considering a cut off of CSF lactate of 30 mg/dL, the sensitivity and specificity for bacterial meningitis were 84.1% and 99%, respectively. In the cytological and biochemical CSF analysis, CSF lactate was the most accurate marker for bacterial meningitis.